Developing a Model of Supplementary English Materials Based on Local Content - Nurliana Nurliana (English Department - University of Sultan Ageng Tirtayasa, 2019)
This research was intended to develop a model of supplementary English materials based on local content for the eighth-grade students of SMP Negeri 9 Palangka Raya in the second semester. In this research, the researcher adapted the development model proposed by Sugiyono (2013:298) with the following steps: need assessment, data analysis, reference of the research, development of a model of supplementary English materials, expert validation, revision, try-out of the model, revision, and final product. The instruments used in this research consisted of questionnaire, interview, and observation. The data obtained were analyzed and described qualitatively. The final product of this research was a model of supplementary English materials based on local content. The materials were divided into three units. The first unit was about descriptive text, particularly about describing things which included traditional musical instruments and weapons from Central Kalimantan. The second unit was about recount text, particularly about retelling experience in visiting tourism places in Central Kalimantan, especially Palangka Raya. The third unit was about narrative text, particularly about fables from Central Kalimantan.